(untitled) (Journal of the College of Basic Education, 2019)
Khedive Ismail is one of the most important figures in history, which greatly influenced the events of Egypt and changed its situation, especially since the Khedive was influenced by the Western manifestations, the most prominent of these manifestations and reforms are the educational aspect, the establishment of the first schools for girls desire to develop Egyptian society and progress, This project has been criticized, but it has been able to achieve the basic blocks to educate the Egyptian girl and make them able to cope with life changes, and took the participation of men in different fields graduated from schools and colleges and became a doctor and engineer, writer and lawyer and others.